Ways to optimize long-distance, local and suburban passenger transportation in modern conditions - Vakhitova, Л.В.; Altayeva, Ж.Ж.; Utegenov, Д.Н.; Sagymbayev, Т.А. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
In this article, the authors consider the issue of optimizing passenger transportation by rail in terms of competition with other modes of transport that carry passengers both on the territory of Kazakhstan (local and suburban passenger transportation) and in the international direction. The analysis of the current state of passenger transportation in the Republic of Kazakhstan is carried out, divided by types of transport. The trends of changes in passenger traffic by the main modes of transport of the Republic of Kazakhstan are studied. The main priority directions of the development of railway passenger transport are highlighted, which can increase the demand for passenger transportation. The foreign experience of implementation and features of implementation of projects of high-speed and high-speed movement of passenger trains of developed countries are considered. Recommendations of the most cost-effective approach to increasing the speeds of passenger trains on the railway transport network are presented.